Konsep Pemikiran Ekonomi Ibnu Khaldun dan Keterkaitannya dengan Teori Ekonomi Masa Kini (Studi Analisis Konsep Ekonomi dalam Kitab Muqaddimah) - Dwi Septianingrum; Hendestri Br Sembiring; M. Faisal Haririe; Sawaluddin Harahap; Fitri Hayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research discusses Ibn Khaldun's economic thought in Muqaddimah and its relationship with modern economic theories. Ibn Khaldun developed an economic approach that integrates with the social, political, and moral aspects of society, emphasizing the importance of social solidarity (asabiyyah), the role of the state in maintaining distribution justice, and the rejection of economic practices that harm society. Some key concepts such as the cycle of civilization, work specialization, and proportional tax policy show that Ibn Khaldun's ideas far predate Western economic thinkers. The methodology used in this research is a literature study with a qualitative approach, using Ibn Khaldun's original works and relevant academic literature. The results of the study show that Ibn Khaldun's thought is still very relevant in facing economic challenges today, especially in terms of justice, ethics, and sustainability. Therefore, his thoughts should be used as a foothold in formulating economic policies that are more inclusive and oriented to the welfare of society.